HR Development in Comfortable Coffee Eatery in Sragen - Mariska Iva Liana; Syairabilla Elmasa Eyatena; Amanda Putri Azkia; Iriani Ismail (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to evaluate the training and development of human resources at Nyaman Coffee Eatery, focusing on enhancing customer service quality through employee competence development. Based on the definition of training as a structured process aimed at improving individual performance, and development which includes the design of learning materials, this research highlights the importance of setting clear training objectives, ensuring adequate trainer qualifications, ensuring material relevance, and applying suitable training methods. The findings show that training at Nyaman Coffee Eatery is focused on developing communication skills, customer service, and teamwork, using on-the-job training methods. Furthermore, an experiential learning approach and job rotation are implemented to increase employee flexibility and skills across various positions. The impact of this training is reflected in increased employee engagement and their ability to provide better service to customers, which ultimately contributes to improved service quality. This research recommends the need for continuous evaluation to assess the long-term effectiveness of the training programs and suggests collaboration with educational institutions to ensure that training materials remain relevant and up-to-date. Overall, this study emphasizes the importance of investing in human resource development for the sustainability and success of Nyaman Coffee Eatery.